2007
DOI: 10.1002/cbdv.200790230
|View full text |Cite
|
Sign up to set email alerts
|

Two New Antibacterial Sesquiterpenoids from Centipeda minima

Abstract: Two new guaiane-type sesquiterpene lactones, compounds 1 and 2, along with three known guaianolide- or pseudoguaianolides, were isolated from Centipeda minima (whole plant). Their structures were identified by spectroscopic and mass-spectrometric analyses. The configuration at C5 of the guaiane framework of 1 was rationalized by quantum-mechanical calculations (Table 2). All compounds were found to be active against eight different microbial pathogens (Table 3), with MIC values in the range of 6.25-100 microg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[94,96]; Asiaticoside B [93,97]; Isomadecassoside [98]; Quadranoside IV, Quercetin, Astragalin, Isoquercetrin [94]; Centelloside E-G, 11-oxo-Asiaticoside B, 11-oxo-Madecassoside, 11(β)-Methoxy asiaticoside B, 11(β)-Methoxy madecassoside, Centellasaponin A, Isoasiaticoside, Scheffoleoside A [93]; 2α,3β,20,23-Tetrahydroxyurs-28-oic acid [99]; Ursolic acid lactone, Ursolic acid, Pomolic acid, Epi-maslinic acid, Corosolic acid, Rosmarinic acid [95]. [111]; Microhelenalin B and C, Arnicolides B-D, Helenalin-angelate, Helenalin-isovalerate, Helenalin-isobutyrate, Helenalin-3-methyl-2-butanoate, Minimolide E, Minimolide B, 2α-Methoxy-6α-angeloyl-2,3-helenalin [101]; Caloinophyllin A, Nobiletin, Quercetin pentamethyl ether, 3 ,4 5,7-Tetramethoxyflavone, 4 ,5,7-Trimethoxyflavone, 1,5-Dihydroxyxanthone, 1,8-Dimethoxy-2-hydroxyxanthone, 1,6-Dihydroxy-7-methoxyxanthone, 4-Methoxycaffeic acid [112].…”
Section: Canadamentioning
confidence: 99%
“…[94,96]; Asiaticoside B [93,97]; Isomadecassoside [98]; Quadranoside IV, Quercetin, Astragalin, Isoquercetrin [94]; Centelloside E-G, 11-oxo-Asiaticoside B, 11-oxo-Madecassoside, 11(β)-Methoxy asiaticoside B, 11(β)-Methoxy madecassoside, Centellasaponin A, Isoasiaticoside, Scheffoleoside A [93]; 2α,3β,20,23-Tetrahydroxyurs-28-oic acid [99]; Ursolic acid lactone, Ursolic acid, Pomolic acid, Epi-maslinic acid, Corosolic acid, Rosmarinic acid [95]. [111]; Microhelenalin B and C, Arnicolides B-D, Helenalin-angelate, Helenalin-isovalerate, Helenalin-isobutyrate, Helenalin-3-methyl-2-butanoate, Minimolide E, Minimolide B, 2α-Methoxy-6α-angeloyl-2,3-helenalin [101]; Caloinophyllin A, Nobiletin, Quercetin pentamethyl ether, 3 ,4 5,7-Tetramethoxyflavone, 4 ,5,7-Trimethoxyflavone, 1,5-Dihydroxyxanthone, 1,8-Dimethoxy-2-hydroxyxanthone, 1,6-Dihydroxy-7-methoxyxanthone, 4-Methoxycaffeic acid [112].…”
Section: Canadamentioning
confidence: 99%
“…This led to our deduction that IF might possess similar apoptotic activity. However, other than a report on the sensitivity Gram-positive bacteria [ 8 ], no other information has reported such activity in IF.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is used in the Chinese folk medicine to treat nasopharyngeal carcinoma (NPC) [ 3 , 4 ]. Recent pharmacological interest has focused on its anti-allergy and anti-bacterial effects [ 5 , 6 , 7 , 8 ]. Phytochemical studies of its composition have led to the identification of a number of terpenes, including sesquiterpene lactones and triterpenes [ 5 , 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological research suggests that active compounds isolated from medicinal plants have multiple pharmacological effects [ 2 , 3 , 4 ]. At present, it has been reported that medicinal plants have been proven to have anti-inflammatory [ 5 , 6 ] and antibacterial [ 7 , 8 ] effects, according to traditional Chinese medicine books, and these compounds also have a wide range of antitumor effects, which can inhibit the proliferation of nasopharyngeal cancer [ 9 ], gastric cancer [ 10 ], colon cancer [ 11 ] and other tumors and induce tumor cell apoptosis. Arnicolide C is a sesquiterpene lactone [ 12 ] isolated from C. minima .…”
Section: Introductionmentioning
confidence: 99%